Capturing touch in parent–infant interaction: A comparison of methods. (29th March 2021) - Brzozowska, Alicja; Longo, Matthew R.; Mareschal, Denis; Wiesemann, Frank; Gliga, Teodora
Abstract: Naturally occurring high levels of caregiver touch promote offspring development in many animal species. Yet, caregiver touch remains a relatively understudied topic in human development, possibly due to challenges of measuring this means of interaction. While parental reports (e.g., questionnaires, diaries) are easy to collect, they may be subject to biases and memory limitations. In contrast, observing touch in a short session of parent–child interaction in the lab may not be representative of touch interaction in daily life. In the present study, we compared parent reports (one‐off questionnaires and diary) and observation‐based methods in a sample of German 6‐ to 13‐month‐olds and their primary caregivers ( n = 71). In an attempt to characterize touching behaviors across a broad range of contexts, we measured touch both during play and while the parent was engaged in another activity. We found that context affected both the quantity and types of touch used in interaction. Parent‐reported touch was moderately associated with touch observed in parent–child interactions and more strongly with touch used during play. We conclude that brief one‐off questionnaires are a good indicator of touch in parent–child interaction, yet they may be biased toward representing particular daily activities and particular types of touch.